The influence of tax regimes on distribution police of corporations: Evidence from German tax reforms - Deborah Schanz; Holger Theßeling (Arbeitskreis Quantitative Steuerlehre (arqus), 2011)
For more than 50 years, researchers around the world have been searching for a solution to Blacks famous 'dividend-puzzle'. However, despite tremendous efforts in different fields of economics, the influence of taxation on the distribution policy of firms has remained elusive and is still subject to extensive debate amongst scholars, professionals and politicians alike. In this paper, we try to shed some light on the discussion by presenting new empirical evidence from German tax reforms. Using a sample containing all firms listed at the Frankfurt stock exchange in the years from 1993 to 2009, we find robust evidence, that the switch from a split-rate tax system with full imputation to a shareholder relief system in 2002 and the change to a flat tax system in 2009 led to significant changes in the payout behavior of German firms. In line with the 'traditional view' of dividend taxation, German decision-makers cut back their dividend payments in response to the reduced advantageousness of dividends in comparison to capital gains after the reform.
Keywords: G30; G35; H24; H25; 330; Dividends; Taxation; Payout Policy